2018
DOI: 10.1001/jamainternmed.2018.0190
|View full text |Cite
|
Sign up to set email alerts
|

State Firearm Laws and Interstate Firearm Deaths From Homicide and Suicide in the United States

Abstract: IMPORTANCE Firearm laws in one state may be associated with increased firearm death rates from homicide and suicide in neighboring states. OBJECTIVE To determine whether counties located closer to states with lenient firearm policies have higher firearm death rates. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study of firearm death rates by county for January 2010 to December 2014 examined data from the US Centers for Disease Control and Prevention for firearm suicide and homicide decedents for 3108… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 60 publications
4
77
0
Order By: Relevance
“…Homicide in the US occurs at higher rates in higherdensity southeastern and midwestern states, and nurses may be less able to intervene directly to prevent homicides in the way they can with suicides in clinical care. At a population level, homicides are associated with poverty, social inequality, unemployment, racial segregation, and other forms of socioeconomic resource deprivation [9,[13][14][15]. Victims of homicides are disproportionately young adults, male, residents of urban areas, and racial/ ethnic minorities [2,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homicide in the US occurs at higher rates in higherdensity southeastern and midwestern states, and nurses may be less able to intervene directly to prevent homicides in the way they can with suicides in clinical care. At a population level, homicides are associated with poverty, social inequality, unemployment, racial segregation, and other forms of socioeconomic resource deprivation [9,[13][14][15]. Victims of homicides are disproportionately young adults, male, residents of urban areas, and racial/ ethnic minorities [2,50].…”
Section: Discussionmentioning
confidence: 99%
“…Firearms play a significant role in both suicides and homicides, and there have been several recent studies on firearm policy and other sociodemographic factors associated with firearm-related and overall injury mortality [4][5][6][7]. While these studies have identified the role of some important social and policy factors in states that can affect injury mortality, a key factor that has been understudied is the role of the healthcare system [8][9][10][11][12][13][14]. Healthcare resources play a critical role in injury outcomes in two ways: (1) prevention of violence against self or others (e.g., mental health services, psychiatric emergency care, wellness promotion and risk assessment) and (2) post-injury care that saves lives and prevents immediate mortality (e.g., trauma and emergency services, inpatient care, follow-up and rehabilitative care) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…We approach this topic from purely a public health perspective. Based upon the preponderance of evidence we wish to emphasize the point, as others have, that reducing access to lethal means will almost certainly save many lives that might otherwise be lost to suicide [67,90,91,95,106,111]. Reducing access to lethal means as involves firearms in particular can take many forms, ranging from individual to community to legislative initiatives.…”
Section: Identifying the Most Effective Firearm Safety Measuresmentioning
confidence: 99%
“…Perhaps not surprisingly then, by some reports, "empirical analysis suggest[s] that firearms regulations which function to reduce overall gun availability have a significant deterrent effect on male suicide, while regulations that seek to prohibit high risk individuals from owning firearms have a lesser effect" [131]. So in some cases, additional proactive safety measures to reduce access to lethal means may be necessary to truly minimize suicide deaths and maximize public health, and there are many rigorous analyses suggesting that these kinds of additional safety measures are effective for reducing suicides, saving lives, and promoting health equity [90,91,95,106].…”
Section: Identifying the Most Effective Firearm Safety Measuresmentioning
confidence: 99%
“…Indeed, decades of research using a variety of methodological and analytical strategies have demonstrated that stricter firearm legislation is associated with lower suicide rates (Boor & Bair, 1990;Fleegler, Lee, Monuteax, Hemenway, & Mannix, 2013;Ludwig & Cook, 2000). Such findings have been replicated and expanded upon several times in recent years, with multiple independent research groups reporting that firearm legislation is associated with lower overall suicide rates both cross-sectionally and longitudinally, and both when laws are considered individually and when they are measured using an aggregated score of the overall strength of firearm legislation (Alban et al, 2018;Anestis, Selby, & Butterworth, 2017;Jehan et al, 2018;Kaufman, Morrison, Branas, & Wiebe, 2018;Kivisto & Phalen, 2018). Research examining individual laws has focused primarily on universal background checks, mandatory waiting periods and, more recently, extreme risk protection orders.…”
Section: Introductionmentioning
confidence: 99%